Nigeria-United States Economic Relations and the Development of the Oil Sector - Okorie, Ikechukwu; Iwuozor, Obialor; Itumo, Anthony (African Journal of Politics and Administrative Studies, 2024)
This study examines Nigeria – United States economic relations from 1999-2018. It was noted that since the Nigeria’s economic relation with United States, the development stride which Nigeria state so desired in the oil sector did not yield any tangible result within the period under study viz opening of new refineries and effective turn around maintenance of the refineries. The specific objectives of this study are: 1. To examine whether Nigeria-United States economic relations has led to opening of new indigenous refineries in Nigeria 2.To determine whether Nigeria–United States economic relations improved the maintenance of refineries in Nigeria within the periods under study 3.To ascertain if Nigeria and United States economic relations had advanced technological transfer in the oil sector industry in Nigeria. The data employed for the study were collected from documentary sources while content analysis was implored for data analysis. The theoretical framework that anchored this study is the Rentier State Theory (RST). After a critical analysis, the following findings were made: 1. it was discovered that Nigeria United States economic relations did not lead to opening of new indigenous refinery 2. The crude oil export to the United States did not improve the maintenance of oil refinery in Nigeria 3. The Nigeria-United States economic relations had not advanced technological transfer in the oil sector industry in Nigeria. In line with the findings the researcher made the following recommendations: 1.That Nigeria government should make a policy that will bring a paradigm shift from net import to net export 2. Nigerian government should make it policy easier as to accommodate and encourage private sector participation in the refining of petroleum products 3. Nigeria government should partner with other countries of the world outside United States that are willing to develop her indigenous technological skills.
Keywords: Crude oil; Development; Economic Relations; Oil sector; Petroleum

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Legal Framework on Protection of Environmental and Foreign Direct Investment Rights in Nigeria: A Reflection on the Oil and Gas Industry - Osaro, Ebiemere (African Journal of International Energy & Environmental Law, 2023)
It is trite that environmental challenges remain one of the major global concerns and no doubt of great impact on human existence and wellbeing. This impact is a result of human activities on the natural ecosystem. This article examines the legal framework by the Nigerian state in regulating the activities of the multinational investors in the oil and gas industry in the Niger Delta region of the country. It discusses the international, regional, and national legal framework in the protection of environment and environmental rights of the host community and foreign direct investment rights. The author demonstrates the imbalance in the protection of environmental and foreign direct investment rights from which suggestions are made towards correcting this injustice as caused by the existing legal framework.
Keywords: Community; Direct; Environment; Foreign investment; Niger Delta; Oil and Gas Industry; Protection; Rights

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry